A content analysis from a US statewide survey of memorable healthcare decisions for individuals with intellectual disability - Fisher, Kathleen M. (2009)
BACKGROUND: Little is known about surrogate healthcare decision-making for individuals with intellectual disability (ID). This study examined healthcare decision-making by residential-agency directors to learn their process and the extent to which the individual is included. METHOD: Content analysis of qualitative data from a mailed survey of residential-agency directors in a large US mid-Atlantic state. RESULTS: Narrative comments of 102 directors (65% of respondents) are reported. Three themes emerged: (a) Identifying someone else’s “best interest” is challenging; (b) Perceptions of the healthcare community, especially related to quality of life, can influence care provided; and (c) Surrogate decision-making is a team effort. CONCLUSIONS: With knowledge of how decisions are made, the healthcare community can better interact with the complex array of service agencies and persons who determine care for this vulnerable population.